SOCS-1 ameliorates smoke inhalation-induced acute lung injury through inhibition of ASK-1 activity and DISC formation - Zhang, Leifang (Clinical immunology (Orlando, Fla.), 2018)
Copyright © 2017 Elsevier Inc. All rights reserved.